“Efecto antimicótico in vitro del extracto hidroalcohólico de la semilla de Persea Americana Mill en cepas de Cándida albicans - Mantilla Roldan, Jessica Mileni (2017)
The objective was to determine the in vitro antifungal effect of the hydroalcoholic extract of the seed of Persea americana Mill. In strains of Candida albincans ATCC 10231. The minimum inhibitory concentration (MIC) was evaluated by the method of microdilution in BHI medium and minimum fungicidal concentration (CMF) by the UFC agar diffusion method. The result obtained for CMI was at the concentration of 312.5 μg / ml in which no greater turbidity formation was observed. With respect to the CMF, a concentration of 2500 μg / ml resulted in a percentage of inhibition of> 99% with a statistically significant difference p <0.005. This effect may be due to the metabolites present in this seed reported by several phytochemical studies such as flavonoids, lactone compounds, tannins and quinones that act by inhibiting the germination of conidia of the fungus. It was concluded that the hydroalcoholic extract of the seed of Persea americana Mill has a moderate antifungal activity (MIC of 100 to <500 μg / mL) in vitro in strains of Candida albicans